Library Usage by the Medical Students of a Tertiary Medical College in Chattogram - Ata, Maliha; Hoque, Rozina; Mostafa, Asma; Barua, Happy Rani (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2020)
Background: The medical college library plays an important role in enhancing theacademic achievements of medical students. In order to improve the quality oflibrary services this study provided an assessment of the impact of the libraryservices on undergraduate medical student learning behavior. Materials and methods: This was a cross-sectional descriptive type of study. Thestudy used a self-designed questionnaire. The study sample was 200 undergraduatemedical students. The questionnaire was administered to them at the end of theirlecture class. Results: The primary reason for going to the library was self study (68%) refer text(37%) and group study (36%). Only 38.55% of the respondents visited the library ona daily basis, 50.5% students visit library when necessary and 10.5% student uselibrary 2-3 times a week. All students (100%) are aware about availability of textbooks in the library. 60.5% students know that journals are available in their library,52% know about dictionaries, 56.55% know of having internet, 62.5% students knowthat computers are available in library. 46.5% students said that their internet ofinstitutional library is somewhat helpful. Noise (67.5%), insufficient space (66%),lack of interent access (46%) and lack of computers(44.5%) might have negativeinfluence on the students in library visit. Conclusion :The study suggested that fulfillment of more needs to be done topromote self directed learning. The usage of library, its resources and services needto be increased. Chatt Maa Shi Hosp Med Coll J; Vol.19 (1); January 2020; Page 38-42